Tracing electron solvation in Li−(NH3)n clusters with K-shell photodetachment spectroscopy - Kryzhevoi, Nikolai V.; Tarantelli, Francesco; Cederbaum, Lorenz S. (Chemical physics letters, 2015)
We demonstrate that K-shell photoelectron spectroscopy is sensitive to binding motifs of cationic cores with excess electrons in solvated metals. Hereby, the satellites in core-level spectra and not the main line provide the important insight into ion-pairing effects. We found that contact ion-pairs in Li−(NH3)1-3 and a solvent-separated ion-pair in Li−(NH3)4 result in remarkably different Li1s spectra. The former spectra have numerous intense satellites of a charge-transfer character while that of Li−(NH3)4 contains only one strong satellite describing excitation of a solvated electron. We also explored K-shell photodetachment of the bare Li− and found that three-electron processes are essential here.
Im Titel erscheint bei der chemischen Formel das "-" hochgestellt und die 3 sowie das "n" tiefgestellt
Gesehen am 02.06.2020